1999
DOI: 10.1159/000017412
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol Exposure Reduces Spinal Cord Motoneuron Number in the Fetal Rat but Does Not Affect GDNF Target Tissue Protein

Abstract: Fetal rats were exposed throughout gestation to one of three diets: an ethanol-containing liquid diet, a liquid diet with the isocaloric substitution of sucrose for ethanol or a laboratory chow control diet. At postnatal day 1 (P1), the spinal cords were taken for analyses of motoneuron number and size. These analyses revealed a significant loss of motoneurons and a reduction of motoneuron size in the ethanol-exposed animals, compared to both sucrose and chow controls. Spinal cord length and ventral horn volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…However, several studies suggest different sensitiveness to ethanol of cranial and spinal motoneurons [36], [37], [38]. Using other animal models, some authors have shown that ethanol exposure during gestation causes a significant loss of motoneurons and a reduction of motoneuron diameter [39]. Different windows of exposure and doses might explain the discrepancy between our results and those mentioned before.…”
Section: Resultscontrasting
confidence: 88%
“…However, several studies suggest different sensitiveness to ethanol of cranial and spinal motoneurons [36], [37], [38]. Using other animal models, some authors have shown that ethanol exposure during gestation causes a significant loss of motoneurons and a reduction of motoneuron diameter [39]. Different windows of exposure and doses might explain the discrepancy between our results and those mentioned before.…”
Section: Resultscontrasting
confidence: 88%
“…Exposure during all gestational periods has dramatic teratogenic consequences 131-133. There are reports of a decrease in spinal and cranial motor neuron production and size, neocortical and hippocampal dysgenesis, increased neuronal cell death, reduced or delayed neuronal migration and a decrease in myelination 134-137. Ethanol exposure also disrupts the integrity of plasma membrane receptors 138, 139.…”
Section: Effects Of Legal Drugs Of Abusementioning
confidence: 99%
“…Some examples of neurological dysfunction and developmental disturbances include reductions in spinal and cranial motor neuron production and size (Barrow Heaton et al 1999); disturbance of neurogenesis and/or gliogenesis in the neocortex (Miller and Robertson 1993), cerebellum (Shetty and Phillips 1992), and hippocampus (Redila et al 2006); increased neuronal cell death (Olney et al 2000); abnormal neuronal migration and decreased myelination (Ozer et al 2000); disruptions in the integrity of plasma membrane NMDA receptors (Honse et al 2003; Hughes et al 2001); adverse effects on the endocrine and immune system (Zhang et al 2005; Wilcoxon et al 2005); and dysregulation of the hypothamic-pituitary-adrenal (HPA) axis (Glavas et al 2007), which can lead to increased responsiveness to later stressors and reduced plasticity in the hippocampus (Sliwowska et al 2010). …”
Section: Neuroimaging Of Prenatal Exposure To Alcoholmentioning
confidence: 99%